Recombinant fusion protein by lysozyme and antibacterial peptide enhances ischemic wound healing via angiogenesis and reduction of inflammation in diabetic db/db mice - Wei Li; Yu-Xin Jiang; Qing-Ying Chen; Guo-Guang Wang (PeerJ, 2021)
Background & aims Lysozyme and antibacterial peptides have been reported to broad-spectrum antibacterial activity and can further improve wound healing. The aim of this study was to assess the effectiveness of a recombinant fusion protein created by combining lysozyme and an antibacterial peptide in forming new vessels and wound healing in an ischemic hind limb. Methods An ischemic hind limb model was established by isolation and ligation of the femoral artery in diabetic db/db mice. Cutaneous wounds were created with or without ischemia. Adductor muscles and wounds were treated with or without the fusion protein. Results The fusion protein accelerated ischemic diabetic wound healing and attenuated impairment of ischemic adductor muscle . Further, the fusion protein elevated expression of platelet derived growth factor (PDGF) and vascular endothelial growth factor (VEGF) protein and mRNA in ischemic adductor muscle, reduced levels of tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6) in serum and expression of phosphorylated nuclear factor κB (p-NF-κB) and p-IKB α in ischemic adductor. The fusion protein also enhanced levels of phosphorylated VEGF and PDGF receptors in the ischemic adductor muscles from diabetic db/db mice. Conclusion The data showed that the beneficial effects of the fusion protein on ischemic wound healing may be associated with angiogenesis and reduction of inflammatory response in the ischemic adductor muscles of diabetic db/db mice.